RELAWAN PAJAK: BAGAIMANA PELATIHAN PAJAK MEMPENGARUHI KEPUASAN WAJIB PAJAK PADA MASYARAKAT URBAN? (STUDI PADA TAX CENTRE UNIVERSITAS PEMBANGUNAN JAYA) - Agustine Dwianika; Irma Paramita Sofia (Universitas Pamulang, 2019)
AbstractIn many countries, taxes are very important for the running of the wheels of government activities. In Indonesia, most of the development budget comes from tax. Therefore tax compliance is very important for the important activities sustainability that have been scheduled. A way to improve tax compliance is to create awareness of taxes early on, continuously and facilitate payment methods or tax reporting by taxpayers. Various ways are carried out by the government to improve taxpayer compliance, including with early tax education and involving young people (millennial) in higher education with the existence of the Relawan Pajak Program (RP). The RP program in the Tax Center (TC) includes several stages, such as socialization, recruitment, training, placement and service also ends with evaluation. The survey conducted by this researcher looked at the effectiveness aspects of the training conducted by TC in collaboration with the Direktorat Jendral Pajak (DJP) in the area of urban society. As a result, training for the effective of RP to help individual taxpayers, but not for corporate taxpayers. So that further, both TC and DJP need to expand the RP training program related to mentoring corporate taxpayer reporting.